Hubungan Inovasi Produk Makanan Terhadap Minat Beli Masyarakat di Gresik - Asmoro, Akbar Ariza; indrarini, rachma (Universitas Negeri Surabaya, 2021)
The product is subjective knowledge from the producer that can be offered in an effort to achieve goals through fulfilling customer needs and desire in accordance with their capacity and purchase power. About the product then the more noticed aspect is product innovation. Product innovation is the key to winning business competition. This research has a purpose to find the relationship of food products innovation to people's buying interests in Gresik using a simple correlation analysis method to analyze data and use spss program version 24 to process data. This research uses 1 independent variable namely product innovation and 1 dependent variable that is buying interest. The data was obtained from a questionnaire that has been shared with 100 respondents, namely the gresik city community selected through purposive sampling techniques and measured on a likert scale. The results found that food product innovation has a significant strong relationship to people's buying interests in Gresik.